2010
DOI: 10.1530/eje-09-1024
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of antihypothalamus and antipituitary antibodies in amateur boxers: is chronic repetitive head trauma-induced pituitary dysfunction associated with autoimmunity?

Abstract: Objective: Current data clearly demonstrate that sports-related chronic repetitive head trauma due to boxing might result in hypopituitarism. However, the mechanism of sports-related traumatic brain injury-induced pituitary dysfunction is still unclear. In order to understand whether autoimmune mechanisms could play a role in the pituitary dysfunction due to sports-related head trauma, we investigated the presence of antipituitary antibodies (APAs) and antihypothalamus antibodies (AHAs) in amateur boxers. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 35 publications
4
41
0
4
Order By: Relevance
“…Further, Tanriverdi et al have shown development of both anti-hypothalamus and anti-pituitary antibodies in boxers exposed to RTBI, which has been attributed to ongoing pituitary dysfunction. 85 Significant decrease of the size of pituitary at 72 h following injury could be the result of cell death, and the subsequent increase in size could be indicative of the recovery of cell populations within the pituitary. The pituitary is a homeostatic tissue that can adjust the percentage of cell populations and size in response to stimuli by upregulating production and differentiation of stem cell populations within the gland.…”
Section: Potential Mechanisms Of Damage and Recovery Of The Pituitarymentioning
confidence: 99%
“…Further, Tanriverdi et al have shown development of both anti-hypothalamus and anti-pituitary antibodies in boxers exposed to RTBI, which has been attributed to ongoing pituitary dysfunction. 85 Significant decrease of the size of pituitary at 72 h following injury could be the result of cell death, and the subsequent increase in size could be indicative of the recovery of cell populations within the pituitary. The pituitary is a homeostatic tissue that can adjust the percentage of cell populations and size in response to stimuli by upregulating production and differentiation of stem cell populations within the gland.…”
Section: Potential Mechanisms Of Damage and Recovery Of The Pituitarymentioning
confidence: 99%
“…[5][6][7][8][9][10][11] In human TBI, however, autoimmunity has only been examined in a limited way and focused on autoantibodies against preselected antigens such as MBP, S100b, and glutamate receptors. [12][13][14][15][16][17][18] Among investigators in the areas of autoimmunity and biomarkers, [19][20][21][22][23] Tanriverdi and associates 20 showed the presence of antipituitary antibodies in patients serum 3 years after head trauma. In other investigations, 24,25 Marchi and colleagues 25 demonstrated that antiglial protein S100b autoantibody levels are elevated in football players with repeated concussions.…”
Section: Introductionmentioning
confidence: 99%
“…Part of this variation may be ascribed to diagnostic difficulties, including those caused by the stress of severe illness, but may also in some cases be related to medication effects, and lack of test re-test reproducibility. It is therefore often recommended that neuroendocrine evaluation should be performed no earlier than one year post trauma unless the clinical picture indicates otherwise Ho, 2007;Tanriverdi et al, 2011). Another important issue is which patients that should be considered for neuroendocrine evaluation.…”
Section: When Should Testing and Treatment Be Considered In Patients mentioning
confidence: 99%
“…Newer studies have, however, indicated otherwise, and overlooking the condition in case of the life-threatening adrenal insufficiency after brain trauma may be fatal (Schneider et al, 2007a). Thus, chronic anterior pituitary hormone deficits have been described with a higher frequency than previously anticipated and have caused expert panels to propose recommendations for routine assessment of pituitary function after TBI with appropriate replacement of insufficient axes Ho, 2007;Tanriverdi et al, 2011). Most populations have a high incidence of TBI of more than 100 in 100,000 inhabitants.…”
Section: Introductionmentioning
confidence: 99%